1977
DOI: 10.1111/j.1748-1716.1977.tb06001.x
|View full text |Cite
|
Sign up to set email alerts
|

Fever and Behavioural Temperature Regulation in the Frog Rana esculenta

Abstract: The skin and colonic temperatures were recorded in frogs (Rana esculenta) which had selected a suitable microenvironment in a box filled with 2-3 cm water. The water temperatures ranged from 0 degrees C to + 40 degrees C. Such measurements were performed before and after intraperitoneal injections of killed pathogenic bacteria (M. xenopi and M. range), killed non-pathogenic bacteria (M. aquae II) and 0.9% sterile saline, intraperitoneal injections of blood plasma from frogs pre-injected with killed M. ranae, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 21 publications
2
31
0
2
Order By: Relevance
“…Myhre et al (1977) demonstrated an increase of final thermal preferendum in frog Rana esculenta, injected with blood plasma from frogs pre-injected with pathogenic bacteria M. ranae (Myhre et al, 1977). Also, lizards Dipsosaurus dorsalis developed behavioral fever after injection of supernatant collected from ex vivo incubated leukocytes isolated from peritoneal cavity of lizards pre-injected with dead A. hydrophila or 3% thioglycollatesaline solution, as well as from rabbits in which fever was previously induced (Bernheim and Kluger, 1977).…”
Section: Evolutionary Conserved Mechanisms Existing Between Fever Of mentioning
confidence: 96%
See 4 more Smart Citations
“…Myhre et al (1977) demonstrated an increase of final thermal preferendum in frog Rana esculenta, injected with blood plasma from frogs pre-injected with pathogenic bacteria M. ranae (Myhre et al, 1977). Also, lizards Dipsosaurus dorsalis developed behavioral fever after injection of supernatant collected from ex vivo incubated leukocytes isolated from peritoneal cavity of lizards pre-injected with dead A. hydrophila or 3% thioglycollatesaline solution, as well as from rabbits in which fever was previously induced (Bernheim and Kluger, 1977).…”
Section: Evolutionary Conserved Mechanisms Existing Between Fever Of mentioning
confidence: 96%
“…Up to date, behavioral fever has been described in all groups of ectothermic vertebrates including reptiles (Bernheim and Kluger, 1976a,b;Burns et al, 1996;do Amaral et al, 2002;Hallman et al, 1990;Kluger et al, 1975;Merchant et al, 2007Merchant et al, , 2008Monagas and Gatten, 1983;Muchlinski et al, 1995;Ortega et al, 1991;Ramos et al, 1993;Vaughn et al, 1974), amphibians (Casterlin and Reynolds, 1977;Kluger, 1977;Murphy et al, 2011;Myhre et al, 1977;Richards-Zawacki, 2010;Sherman et al, 1991), fish (Boltaña et al, 2013;Cabanac and Laberge, 1998;Covert and Reynolds, 1977;Grans et al, 2012;Reynolds, 1977;Reynolds et al, 1976Reynolds et al, , 1978 but also in invertebrates (Campbell et al, 2010;Elliot et al, 2002) and newborn mammals, which in response to bacterial pyrogens are unable to develop fever physiologically but do so behaviorally (Satinoff et al, 1976). However, there have been some contrasting data showing that injection of pyrogens, killed bacteria or parasites in some species of lizards (Don et al, 1994;Hallman et al, 1990;Laburn et al, 1981;Muchlinski et al, 1995;Ortega et al, 1991;Schall, 1990), turtles (Zurovsky et al, 1987b), snakes (Burns et al, 1996;Zurovsky et al, 1987a) and fish …”
Section: Behavioral Fever In Ectothermic Vertebratesmentioning
confidence: 99%
See 3 more Smart Citations